Xystreurys rasilis - Riestra, C. (2020)
This demersal species is distributed from southern Brazil to Argentina. It is taken in commercial fisheries in Uruguay and northern Argentina, which is where its largest global abundance exists. According to stock assessment and fisheries data, there is no decline detected in the demersal stock in Argentina and Uruguay and abundance indices show an increase in recent years (since 2014). Conservation measures in Argentina and Uruguay include a total allowable catch limit and regular monitoring of stock status.Fishing is not expected to be driving declines approaching a threatened or Near Threatened level at this time; therefore, it is listed as Least Concern.